Fault-tolerant trajectory tracking of mobile robots via model-free intelligent PID and fault observer - Sy Phuong Ho; Manh Tien Ngo; Duy Tan Ngo; Dinh Tu Duong; Van Du Phan; Kim Duyen Ha Thi; Thanh Tri Nguyen; Minh Dang Dau; Thu Uyen Le Thi (Institute of Advanced Engineering and Science, 2026)
This paper addresses the problem of unexpected errors, such as model uncertainties and actuator faults, that degrade the performance of wheeled mobile robots (WMR). To overcome these challenges, a fault-tolerant control (FTC) approach is developed in which model-free control (MFC) is merged with an intelligent-proportional integral derivative (i-PID) controller and complemented by a fault observer (FO). Unlike existing approaches, the proposed controller does not rely on accurate system modeling; instead, MFC ensures robustness to time-varying parameters, and while i-PID enhances trajectory tracking through adaptive gain adjustment. The FO estimates actuator faults in real time and compensates for their effects, ensuring reliable operation even under severe conditions. The closed-loop stability is rigorously analyzed via Lyapunov theory. MATLAB/Simulink results show reduced tracking errors, improved stability, and strong robustness under both model uncertainties and actuator faults, including time-varying mass and inertia, validating the effectiveness and practical potential of the proposed FTC.